Legal Challenges in Countering Religion-Based Terrorism in Asia - Rizqa Febry Ayu; Muhammad Ulul Albab; Wahyudi; Moh Ainul Yakin; Imat Hibbatulloh (Mahkota Science Publishers, 2025)
This study aims to enrich the academic discourse on the importance of adaptive legal reform in response to changing times, technological developments, and global and local socio-political dynamics, with a focus in the sustainable, fair, and peace-oriented prevention of religiously motivated terrorism in Asia. In this study, the method used is library research to review, inventory, and analyse scientific literature, legal documents, previous studies, reports from international institutions, and various written sources relevant to the theme of legal challenges in countering religious-based terrorism in Asia. The findings indicate that legal challenges in countering religion-based terrorism in Asia require the courage to break free from the dichotomy between security and freedom, while dismantling the illusion that law is merely a tool of the state. Instead, the complexity of Asian pluralism demands legal innovations that prioritise substantive justice, strengthen dialogue between identities, and dare to acknowledge that true harmony can only be achieved when the state, civil society, and the international community jointly formulate inclusive, reflective, and responsive counter-terrorism strategies that take into account local social dynamics and history because amid the evolving threat of terrorism, Asia's future as a peaceful and just region can only be achieved by placing humanity, equality, and diversity at the heart of every legal policy.